Standardisasi Keselamatan dan Kesehatan Kerja (K3) di Ruang Kerja Praktik Tata Busana pada Kelas XI SMK Negeri 1 Brondong Lamongan - Hafidzah Nabilah A; Mein Kharnolis; Inty Nahari; Peppy Mayasari (Journal on Education, 2023)
This study aims to describe the standardization of OSH in the fashion practice workspace of SMK Negeri 1 Brondong Lamongan, using a qualitative descriptive method, data collection techniques in the form of observation, questionnaires, interviews and documentation. The research instruments used were observation sheets and student response questionnaires totaling 24 students of class XI. The basis for OSH standardization uses the Undang-Undang Dasar Peraturan Pemerintah Republik Indonesia No.1 Tahun 1970 tentang keselamatan kerja. The results of this study indicate that: (1) Observations on the application of OSH in the practical workspace have not met the standards. (2) The participants' responses to the OSH questionnaire obtained results that 1% of students answered disagree, 23% neutral, 58% agreed, and 18% of students answered strongly agreed, with an overall result of 79 which stated that most students had implemented OSH. (3) the factors that influence the implementation of the completeness of Occapational Safety and Health (OSH) standardization are the budget or finance (economy).